The active unbalanced vibration compensation of the flexible switched reluctance motorized spindle. (October 2014) - Qiao, Xiaoli; Zhu, Changsheng
An active unbalanced vibration compensation scheme with built-in force actuator for a flexible switched reluctance motorized spindle (SRMS) is proposed. The force actuator is a set of windings, which are wound on the stator pole of the switched reluctance motor (SRM). The equivalent unbalance identification method is proposed to indentify online the unbalanced vibration caused by the grinding wheel's mass imbalance. The equivalent reference unbalance compensation signal is produced by the identification method, which is used to obtain the compensation current of a force actuator, so a controlled, non-contact electromagnetic compensation force on the rotor of the SRMS is produced by the force actuator to compensate the actively unbalanced vibration of the flexible SRMS. The dynamic flexible SRMS is modeled by means of finite element method (FEM). The inductance of main and control windings, the coefficients of the compensation and the unbalanced magnetic pull force are identified by the FEM, and then the active unbalanced vibration compensation scheme for the flexible SRMS is designed in Matlab, in which inductance of main and control windings, the coefficients of the compensation and unbalanced magnetic pull force are obtained by the Look-up table method. The results show that the proposed active unbalanced force compensation scheme has an obvious compensation effect and the coefficients indentified by the FEM have been closer to an actual effect on compensating the unbalanced vibration of the flexible SRMS.